2009
DOI: 10.1177/0022034509353403
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-induced CCN2: from Smoking to Periodontal Fibrosis

Abstract: Since fibrosis is observed in smokers' gingiva, it was hypothesized that fibrosis was caused by nicotine in the periodontium. Therefore, in this study, we investigated the effects of nicotine on the induction of a profibrotic molecule, connective tissue growth factor (CCN2/CTGF), in human gingival fibroblasts (HGFs) and periodontal ligament (PDL) cells. With 1 microg/mL nicotine, vacuolization and attenuated proliferation were observed. Interestingly, 1 microg/mL nicotine increased the production of CCN2/CTGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
3
23
1
Order By: Relevance
“…In this study, knockdown of CCN2 by CCN2 siRNA strongly reduced the elevated mRNA and protein levels of CCN2 induced by CSE or nicotine and then inhibited the rPASMCs proliferation. These results indicate that CSE and nicotine can induce CCN2 production, which is consistent with other studies [Takeuchi et al, 2010;Wang et al, 2011]. Furthermore, these results reveal that CCN2 plays an important role in the regulation of cigarette smoke-induced rPASMCs proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, knockdown of CCN2 by CCN2 siRNA strongly reduced the elevated mRNA and protein levels of CCN2 induced by CSE or nicotine and then inhibited the rPASMCs proliferation. These results indicate that CSE and nicotine can induce CCN2 production, which is consistent with other studies [Takeuchi et al, 2010;Wang et al, 2011]. Furthermore, these results reveal that CCN2 plays an important role in the regulation of cigarette smoke-induced rPASMCs proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…No patients had taken any antibiotics or anti-inflammatory drugs for 3 months prior to the study. Tissues were obtained according to established procedures [10,19]. Briefly, the gingiva and periodontal ligaments were cut into small pieces.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we cultured human gingival fibroblast cells (HGF) and periodontal ligament (PDL) cells with 1 lg/ml nicotine and found that extracellular matrix (ECM) overproduction could be induced by nicotine stimulation through induction of CCN family protein 2 (CCN2/CTGF) and type I collagen at both RNA and protein levels [10]. In this previous study, we observed nicotine-induced cellular vacuolization and induction of type I collagen that was mediated by the pro-fibrotic molecule CCN2/CTGF, which was confirmed using a neutralizing anti-CTGF antibody.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine has been reported to increase the production of CTGF protein in human gingival fibroblasts and pulmonary artery smooth muscle cells [8,9]. We hypothesized that maternal nicotine exposure could augment neonatal hyperoxia-induced lung fibrosis in rats.…”
Section: Introductionmentioning
confidence: 99%